Body size‐adjusted dose analysis of pirfenidone in patients with interstitial pneumonia. Issue 3 (29th August 2017) - Uehara, Masahiro; Enomoto, Noriyuki; Oyama, Yoshiyuki; Suzuki, Yuzo; Kono, Masato; Furuhashi, Kazuki; Fujisawa, Tomoyuki; Inui, Naoki; Nakamura, Yutaro; Suda, Takafumi
ABSTRACT: Background and objective: Pirfenidone is an effective anti‐fibrotic agent for idiopathic pulmonary fibrosis (IPF). Although adverse events (AE) sometimes prevent patients from continuing treatment, current dose adjustment guidance does not consider patient body size or weight (BW). The aim of this study was to evaluate the importance of pirfenidone dose adjustment by body surface area (BSA) or BW for preventing AE and permitting continuous treatment in patients with interstitial pneumonia (IP). Methods: Sixty‐seven Japanese patients with IP including 46 patients with IPF treated with pirfenidone between 2009 and 2015 were retrospectively evaluated. Pirfenidone doses were adjusted by BSA or BW and were compared with clinical parameters. Results: Forty‐two of 67 patients (62.7%) with IP showed AE, most commonly gastrointestinal symptoms (77.5%). Patients having AE received significantly higher adjusted doses of pirfenidone by both BSA and BW ( P = 0.024 and P = 0.010, respectively), while unadjusted doses did not differ. BSA‐adjusted dose discriminated patients with AE from those without (area under the curve = 0.666 at 1085 mg/m 2 ). Six of seven patients (85.7%) who discontinued pirfenidone due to AE took ≥1085 mg/m 2 of pirfenidone. In a subgroup with IPF, patients taking a medium dose (median: 876 median–1085 mg/m 2 ) showed a lower annual decline in % forced vital capacity than patients taking a lower dose ( P = 0.025). Conclusion: BSA‐adjusted pirfenidone dosing may be useful to prevent AE whilst achieving a long‐term treatment effect in patients with IP. Abstract : See related Editorial Patients with interstitial pneumonia (IP) and adverse effects received a significantly higher dose of pirfenidone adjusted by body surface area and body weight. In a subgroup of patients with idiopathic pulmonary fibrosis (IPF), a high/medium dose was associated with a lower decline in % forced vital capacity (FVC). Body size‐adjusted dosing may be beneficial for the treatment of IP.